Price-Response Asymmetry and Spatial Differentiation in Local Retail Gasoline Markets - Jeremy A. Verlinda (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
This study explores the possibility that local market power influences the observed asymmetric relationship between changes in wholesale gasoline costs and changes in retail gasoline prices. I exploit an original data set of weekly gas station prices in Southern California from September 2002 to May 2003, and take advantage of detailed station and local market level characteristics to determine the extent to which spatial differentiation influences price response asymmetry. I find that brand identity, proximity to rival stations, bundling and advertising, operation type, and local market features and demographics each influence a station's predicted price-response asymmetry.
Keywords: 330